Rendszerváltó évek. Széthullás időrendben - MSzMP 1988. december - 1989. Július, I . Years of Transition in Hungary. Chronology of a Downfall - MSzMP December 1988 - July 1989, I (MTV - Hungarian Television, 1997)
Television program about the political and social issues of the transition period of Hungary.